Rancang Bangun Mesin Penepung Rumput Laut Untuk Industri Rumahan - M. Ridho Firmansyah; Pranowo Sidi; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
This research aiming to make dried seaweed into seaweed flour by using a machine, namely a seaweed flour machine. The reason why this dried seaweed is processed into seaweed flour is because during the COVID-19 pandemic the sales opportunities for processed seaweed products such as seaweed flour and carrageenan are quite large, but the seaweed exported abroad since 2020 is mostly only in the form of only dry seaweed and no further processing. The method used is using the Ulrich method by selecting several design concepts, designing the machine using Fusion 360 software to create drawings, designing, assembling machine components, from the fabrication stage to the machine testing stage to find out the production results of the machine. The material used is mild steel which is given a hard chrome coating for the manufacture of the pounder and the pounder base. Stainless steel is used for the manufacture of hoppers, droppers, flour base machines. ASTM A36 to make the frame structure of the stand, and mild steel which will be used to make the motor pulley casing, bearing house, and locks. The result of flouring dry seaweed using this flour machine is 34.3 kg / hour